Serum-derived host miR-423-5p and miR-378a-3p as molecular markers for severe tuberculosis: a promising prognostic tool for survival - Hurtado, Joaquin; Buroni, María; Giordano, Alvaro; Nin, Nicolas; Hurtado, F. Javier; Tosar, Juan Pablo; Robello, Carlos; Greif, Gonzalo (Frontiers in Tuberculosis, 2024)
Tuberculosis (TB) remains a leading cause of infectious disease-related mortality.Annually, 10 million people contract TB, resulting in 1.5 million deaths, despite being a preventable and curable disease. Severe TB cases necessitate Intensive Care Unit (ICU) admission, with mortality rates ranging from 15.5% to 65.9%. Recent research highlights the role of microRNAs (miRNAs) in infectious disease diagnosis, with studies reporting distinct miRNA profiles in active pulmonary TB and sputum samples. This study aims to identify miRNAs as potential prognostic biomarkers for severe TB in ICU patients.Total RNA was extracted from the serum of ICU TB patients and controls. miRNA libraries were prepared and high throughput sequenced using an Illumina-sequencer. Differential miRNA abundance between patients and controls was analyzed with sRNAtoolbox, and DESeq2 was used for comparisons.Results demonstrated three differentially abundant miRNAs in severe TB patients' serum, validated by RT-qPCR. Stratifying patients by outcome revealed a significant difference in the ratio between two miRNAs: hsa-miR-378a-3p and hsa-miR-423-5p. The analysis showed that a miRNA-423-5p/miRNA-378a-3p ratio less than 27 is associated with a poor prognosis, highlighting its potential as a prognostic indicator of disease severity.These findings are promising and warrant validation, while assessing these biomarkers in non-severe TB settings could further help identify more aggressive forms of the disease.In conclusion, this study explores the potential of circulating miRNAs as prognostic tools for severe TB cases in the ICU, offering a promising avenue for improving clinical decision-making and patient outcomes. Further validation and exploration in diverse TB contexts are essential for comprehensive understanding and application.